A Study on the Socio-economic Factors Influencing Women’s Involvement in SHG Programmes in Ambedkar Nagar District of Uttar Pradesh, India - , Km. Deepshikha; Supriya,; , Sandeep Gautam; , Monmath Gopal; , Avinash Pratap; , Deep Narayan Yadav (Archives of Current Research International, 2024)
In the present paper, an attempt has been made to understand the socio-economic conditions of the SHG members and factors determining women’s participation in the SHG programme, utilizing pre-structured and pre-tested schedules to collect information from Ambekar Nagar district. Employed proportionate random sampling as well as purposive technique, 120 respondents were selected from two blocks i.e., Akbarpur and Bhiti based on higher number of SHGs. The data were analyzed with the help of suitable statistical tools like percentage, mean and binary probit models, to find the factors that effect the women’s participation in SHG programme. Results revealed that 40% of the respondents were illiterate, with the remainder having varying levels of education, predominantly at the primary level. Family size was primarily medium (5-6 members), and landholdings averaged 1.4 hectares, reflecting a predominantly agricultural setting. Livestock ownership, particularly buffaloes and goats, contributed significantly to household livelihoods. The study employed a probit regression model to analyze the determinants of women’s participation in SHGs, with factors such as age, family size, landholding, education, and net non-farm income examined. The results indicated that age and net non-farm income were statistically significant in influencing participation, with older women and those with higher non-farm income being less likely to engage in SHGs. Conversely, larger family size positively impacted participation. The findings suggest that rural development initiatives should prioritize younger women, expand education opportunities, and promote farm-based income generation to enhance SHG participation and, consequently, women's empowerment.